Algal light sensing and photoacclimation in aquatic environments. (11th May 2017) - Duanmu, Deqiang; Rockwell, Nathan C.; Lagarias, J. Clark
Abstract: Anoxygenic photosynthetic prokaryotes arose in ancient oceans 3.5 billion years ago. The evolution of oxygenic photosynthesis by cyanobacteria followed soon after, enabling eukaryogenesis and the evolution of complex life. The Archaeplastida lineage dates back 1.5 billion years to the domestication of a cyanobacterium. Eukaryotic algae have subsequently radiated throughout oceanic/freshwater/terrestrial environments, adopting distinctive morphological and developmental strategies for adaptation to diverse light environments. Descendants of the ancestral photosynthetic alga remain challenged by a typical diurnally fluctuating light supply ranging from 0 to 2000 μ E m −2 s −1 . Such extreme changes in light intensity and variations in light quality have driven the evolution of novel photoreceptors, light‐harvesting complexes and photoprotective mechanisms in photosynthetic eukaryotes. This minireview focuses on algal light sensors, highlighting the unexpected roles for linear tetrapyrroles (bilins) in the maintenance of functional chloroplasts in chlorophytes, sister species to streptophyte algae and land plants. Abstract : Aquatic environments pose daunting challenges for efficient light harvesting and photosynthesis, requiring novel photoacclimation strategies in eukaryotic algae. Recent studies provide new insight into the loss and repurposing of bilin‐based photoreceptors in algae that facilitate responses to inevitable changes in light fluences inherent to their complex light environments.